Analysis of Entropy Generation in Natural Convection of Nanofluid inside a Square Cavity Having Hot Solid Block: Tiwari and Das’ Model - Sheremet M. A. Mikhail Aleksandrovich; Oztop H. F. Hakan; Pop I. Ioan; Abu-Hamdeh N. Nidal (2016, 2016)
Title screen